Measurement of urine protein. (5th April 2022) - Ramsden, Jasmine; Poole, Ruth
Abstract : In this fourth article in our 'Test Tips' series, Jasmine Ramsden and Dr Ruth Poole compare the measurement of urine protein by three tests: urine dipstick testing, albumin:creatinine ratio and protein:creatinine ratio – providing guidance on key practical points to consider.